The influence of age at menarche, menstrual cycle length and bleeding duration on time to pregnancy: a large prospective cohort study among rural Chinese women. (27th January 2017) - Zhang, Q; Wang, YY; Zhang, Y; Zhang, HG; Yang, Y; He, Y; Xu, JH; Zhao, J; Peng, ZQ; Ma, X
Abstract : Objective: To investigate the relations among age at menarche (AAM), menstrual cycle length, menstrual bleeding duration and time to pregnancy in a large cohort of rural Chinese women. Design: A prospective cohort study. Setting: Local family‐planning service agencies and maternal/child care service centres. Population: A total of 391 320 rural women of reproductive age who participated in the National Free Pre‐pregnancy Checkups and were planning to conceive were enrolled. Methods: Menstrual characteristics were collected via face‐to‐face interviews. The Cox proportional hazards model were used to estimate the fecundability ratios (FRs) and 95% confidence intervals for each measure relative to its reference category. Main outcome measures: Time to pregnancy. Results: Women with an AAM later than 14 years of age were less likely become pregnant compared with women with AAM at 13–14 years of age (FR 0.93, 95% CI 0.92–0.94). Those with menstrual cycle lengths >29 days were less likely to come pregnant (FR 0.91, 95% CI 0.90–0.92) compared with the reference cycle length of 27–29 days. Women with bleeding durations of <4 (FR 0.88; 95% CI 0.86–0.91) or >5 days (FR 0.91; 95% CI 0.90–0.91) showed lower FRs compared with those reporting 4–5 days of bleeding. The associations were independent of maternal age, ethnicity, education level, occupation, tobacco use, alcohol use and body mass index. Conclusion: A later onset of menarche, longer menstrual cycle length, both shorter (<4 days) and longer (>5 days) bleeding duration were associated with a lower FR and longer time to pregnancy in rural Chinese women. Tweetable abstract: A later menarche, longer cycle, shorter or longer bleeding duration were associated with lower fecundity. Tweetable abstract: A later menarche, longer cycle, shorter or longer bleeding duration were associated with lower fecundity.